Assessing the effectiveness of community-based targeting of emergency food aid in Bangladesh, Ethiopia, and Malawi - Gilligan, Daniel O.; Hoddinott, John F.; Quisumbing, Agnes R.; Sharma, Manohar (International Food Policy Research Institute, 2005)
...IFPRI examined the effectiveness of community-based targeting following three recent emergencies: the 1998 floods in Bangladesh; the 2002 drought in Ethiopia; and the 2001-02 failed maize harvest in Malawi.